Correlation of self-reported physical activity with pulse wave velocity in male adolescents - Hajime Miura; Saori Maruoka; Megumi Sugino (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Habitual exercise is important for improving or maintaining arterial function with age. However, the role of physical activity on arterial stiffness in adolescents is unclear. This study evaluated the influence of physical activity on the brachial-ankle pulse wave velocity (baPWV) in high school students. The baPWV, brachial systolic blood pressure (SBP), diastolic blood pressure (DBP), and body composition were assessed in 221 healthy male high school students (16.4 ± 1.5 yrs). Self-reported physical activity (PA) was evaluated by the short form of the International Physical Activity Questionnaire (IPAQ-SF). Measurement variables were calculated for four age stages (15, 16, 17, and 18 yrs). The values for baPWV, SBP and DBP increased from 15 to 18 yrs. Stepwise regression analysis showed that SBP (β = 0.496), PA (β = -0.170), age (β = 0.186), and weight (β = -0.133) were independent contributors to baPWV, accounting for 36.6% of the variability. These results support the concept that physical activity lowers baPWV, which indicates an improvement in the arterial function of adolescents as well as middle-aged to elderly people.